Penerapan Teknologi Pengoperasian, Perawatan dan Pelatihan Mikro Hidro di Desa. Karang Suko KecAMATAN Pagelaran KabUPATEN Malang - Muhammad Irfan; Machmud Effendy; Ali Mokhtar; Suwignyo . (Jurnal Dedikasi, 2015)
Penerapan Teknologi Pengoperasian, Perawatan danPelatihan Mikro Hidro di Desa. Karang Suko KecAMATANPagelaran KabUPATEN MalangMuhammad Irfan1, Machmud Effendy2, Ali Mokhtar3, Suwignyo4 1,2,3,4Fakultas Teknik Universitas Muhammadiyah MalangEmail : 1)Irfan_tsd@yahoo.com, 2)machmudeffendy@yahoo.com, 3)alimokhtar011@gmail.com, 4)wignyo_08@yahoo.comABSTRAKMicro hydro power plant ( MHPP ) Sumber Maron located in the village of Karangsuko, districts Pagelaran, Malang district. It has been in operation since 2011. Sustainability Mikro Hidro Power (MHP) system depends on many things , one of them is a good way of operation and proper maintenance. The main problem is the unavailability of operators who are able to overcome with disturbances and maintain of MHP system . The purpose of science and technology program activities for the community is to produce the human resources were able to operate , maintain and overcome the slight disturbance in the MHP system. Methods of science and technology program for community activities was carried out by using PRA ( Participatory Rapid Appraissal ) , which is a method that is both empowering and Bottom - up Participatory Approach , by doing workshops and practice . The material of the workshop is the introduction of the MHP system, the components of MHP, on how to operate , maintain all the resources MHP correctly , how to cope with distraction MHP, and health and safety. The results of this activity is the availability of human resources having appropriate skills standards , start from the basic principles operate , maintain and how to resolve the problem if there is interference on all the resources at MHP.Keywords: MHPP, PRA, Science and Technology